Reconstruction in time-warped weighted shift-invariant spaces with application to spline subspaces - Jun Xian; Yongjin Li (International Journal of Mathematics and Mathematical Sciences)
We discuss the reproducing kernel structure in shift-invariant spaces and the weighted shift-invariant spaces, and obtain the reconstruction formula in time-warped weighted shift-invariant spaces, then apply them to a spline subspace. In the spline subspace, we give a reconstruction formula in a time-warped spline subspace.